Selitrichodes neseri (Hymenoptera: Eulophidae) recovered from Leptocybe invasa (Hymenoptera: Eulophidae) galls after initial release on Eucalyptus (Myrtaceae) in Brazil, and data on its biology - Masson, Marcus V.; Tavares, Wagner de S.; Lopes, Fabricio de A.; Souza, Amanda R. de [UNESP]; Ferreira-Filho, Pedro J.; Barbosa, Leonardo R.; Wilcken, Carlos F. [UNESP]; Zanuncio, Jose C. (Florida Entomological Soc, 2017)
Blue gum chalcid, Leptocybe invasa Fisher & La Salle (Hymenoptera: Eulophidae), causes galling damage to Eucalyptus species (Myrtaceae) in various regions of the world, but has been controlled effectively by its primary parasitoid, Selitrichodes neseri Kelly & La Salle (Hymenoptera: Eulophidae). The objectives of this study were to evaluate the recovery of S. neseri after its initial release on Eucalyptus plants in Brazil and to provide data on its biology. Selitrichodes neseri was imported from South Africa to Brazil for the biological control of L. invasa, in Mar 2015, and recovered from Aug 2015 to Dec 2016. Successful recovery of this parasitoid shows its potential to become established in the field. Seedlings of 2 hybrids obtained from crosses between rose gum Eucalyptus grandis W. Hill. ex Maiden and flooded gum Eucalyptus urophylla S. T. Blake and between Eucalyptus sp. and (river red gum Eucalyptus camaldulensis Dehnh. x E. grandis) showed potential as hosts for culture of S. neseri on L. invasa in the laboratory because up until the adult parasitoid emergence these seedlings did not wilt. When reared at 25.1 to 26.0 degrees C, the total number of parasitoids and the proportion of male parasitoids were highest, relative to hosts reared at 26.1 to 27.0 degrees C. Peak emergence of S. neseri occurred 28 d after parasitism.
Keywords: emergence; exotic pest; gall wasp; parasitoid; South Africa